2016
DOI: 10.18632/oncotarget.13030
|View full text |Cite
|
Sign up to set email alerts
|

Serum APE1 as a predictive marker for platinum-based chemotherapy of non-small cell lung cancer patients

Abstract: PurposeTo define the role of the DNA repair protein apurinic/apyrimidinic endonuclease 1 (APE1) in predicting the prognosis and chemotherapeutic response of non-small cell lung cancer patients receiving platinum-containing chemotherapy.ResultsOur investigations found that serum APE1 level was significantly elevated in 229 of 412 NSCLC patients and correlated with its level in tissue (r2 = 0.639, p < 0.001). The elevated APE1 level in both tissue and serum of patients prior to chemotherapy was associated with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…Thus under certain conditions such as inflammatory response or tumorigenic condition induce secretion of APE1 from cells. Consistent with this idea, elevated levels of serum APE1 and its auto-antibody, have been found to be present in lung cancer patients' [54, 55] The presence of the extracellular APE1, therefore, questions the biological significance of this secretion. Moreover, a recent study has shown that extracellularly secreted APE1/Ref-1 triggers apoptosis in triple-negative breast cancer cells [24].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus under certain conditions such as inflammatory response or tumorigenic condition induce secretion of APE1 from cells. Consistent with this idea, elevated levels of serum APE1 and its auto-antibody, have been found to be present in lung cancer patients' [54, 55] The presence of the extracellular APE1, therefore, questions the biological significance of this secretion. Moreover, a recent study has shown that extracellularly secreted APE1/Ref-1 triggers apoptosis in triple-negative breast cancer cells [24].…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, auto-antibodies against APE1 have been identified in systemic lupus erythematous patients [66]. Recently, the identification of serum APE1 and its auto-antibody, and its differential presence among normal controls and lung cancer patients further indicate APE1 as an autoimmune antigen [54, 55]. Our finding of the secretory APE1 from monocytes upon inflammatory challenges, and its role as a regulator of IL-6 mediated cellular responses marks this protein as a target for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…We recently discovered that APE1 protein is also present in human serum and, more importantly, is elevated in NSCLC patients, and correlates with platinum‐containing chemotherapy responses. When tracing serum APE1 throughout treatment, APE1 levels change during chemotherapy and reflect therapeutic outcomes . Based on this observation, we initiated a trial to monitor changes in serum APE1 levels during EGFR‐TKI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…When tracing serum APE1 throughout treatment, APE1 levels change during chemotherapy and reflect therapeutic outcomes. 25 Based on this observation, we initiated a trial to monitor changes in serum APE1 levels during EGFR-TKI treatment. If a correlation between serum APE1 level and EGFR-TKI response can be observed prior to the actual imaging progression, we could predict resistance events and prophylactically add APE1 inhibitors or other possible interventions by real-time monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] In normal tissues, APE1 becomes upregulated in response to oxidative stress. 12 Upregulation of APE1 has been reported from a multitude of human cancer types, including hepatocellular carcinoma, osteosarcoma, breast, lung, ovarian, colorectal, and bilio-pancreatic cancer [12][13][14][15][16] and has been linked to adverse tumor phenotype and poor patient prognosis in some of them. [17][18][19][20] Consequently, APE1 has recently gained interest as an emerging anti-cancer drug target.…”
mentioning
confidence: 99%